PREPARATION AND STUDY OF THE OPTICAL PROPERTIES OF CORE SHELL POLY 3-hexylthiophene@(SiO2 , ZnO , Ag) NPs (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
The study explores enhancing the optical of core shell polymers by incorporating Poly 3-hexylthiophene@NP (SiO2, ZnO, Ag ) into photo-electro-active layers useful in solar cell applications. These materials were examined and analyzed using various techniques like X-ray diffraction (XRD), scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), Atomic Force Microscopy (AFM), and UV-visible Absorption Spectrum. XRD analysis revealed high crystallinity in Poly 3-hexylthiophene @SiO2, ZnO and Ag, with crystallite sizes between 62.63 – 93.069 nm. UV-visible absorption tests indicated band gap values of 2.3 eV, 2 eV, 2.07 eV, and 2.05eV for Poly1 , Poly2 , Poly3 ,Poly4 respectively the synthesized nanoparticles. The polymeric membrane exhibited varying thicknesses of approximately 15.4 nm, 20.6nm, 10.2 nm, and 5.02 nm, with surface roughness values of 6.48nm, 10.4nm, 5.19nm, and 2.59 nm for Poly1 Poly2 , Poly3 ,Poly4 respectively of the polymer films. Additionally, the polymer film on the nanoparticles varied in thickness from 5.2 nm to 9.3 nm, indicating a thin, transparent layer capable of efficiently transmitting light.